CREATIVE INITIATIVE AND OWN CREATIVITY AS AN INTEGRAL FACTOR OF TEACHER'S ACTIVITIES IN INDIVIDUAL CLASSES - Маскович, Т.М.; Бардашевська, Я.М. (SWorldJournal, 2022)
The article considers the main positions and results of professional development of creativity as a basic component; the use of partnership techniques that promote teacher and student self-development is analyzed